Identification of Child and Youth Maltreatment as Experienced by Prehospital Emergency Care Providers. (2nd November 2021) - Salminen-Tuomaala, Mari; Tiainen, Juha; Paavilainen, Eija
Abstract: This mixed method study explores 200 prehospital emergency care providers' experiences of identifying child and youth maltreatment. The data were collected in Finland in 2019–2020 using an online survey tool and analysed using SPSS statistics and inductive content analysis. Respondents had encountered signs of physical and psychosocial maltreatment, and family challenges, contexts, and economic and social problems indicative of maltreatment. It is important for the early intervention and prevention of long-term mental health problems that prehospital emergency care providers receive continuing education on the identification of child maltreatment.